Draft Genome Sequences of Leptospira santarosai Strains U160, U164, and U233, Isolated from Asymptomatic Cattle - Kremer, Frederico S. (Genome Announc, 2015)
In the present work, we announce the draft genomes for three new strains (U160, U164, and U233) of Leptospira santarosai, isolated from urine samples from asymptomatic cattle in Rio de Janeiro, Brazil.